Bakhtinian Carnivalesque and Paul’s Foolish and Scandalous Gospel - Nygaard, Mathias (Biblical interpretation, 2018)
In this article I read the Pauline gospel through the heuristic prism of Bakhtinian carnivalesque. Such a reading is legitimated by Paul’s acknowledgement that his gospel was a scandal to the Jews and a foolishness to the Greeks (1 Cor. 1.23). As a literary trope carnivalesque can be summarized according to the following points: (1) it entails an unhindered interaction between all people; (2) in it otherwise impermissible behaviour is accepted; (3) it is set towards a uniting of opposites; (4) it explores the sacrilegious; and (5) it constitutes a redefinition of the physical and the bodily. In my argument I show that these aspects are all present in the Pauline literature in various ways. Properly defined, Paul’s gospel is carnivalesque. Altogether, my reading serves as a reminder of some of the subversive aspects of his theological narrative. This further allows me to describe parts of his non-representative and apophatic anthropology.